Polymorphism in Squaraine Dye Aggregates by Self‐Assembly Pathway Differentiation: Panchromatic Tubular Dye Nanorods versus J‐Aggregate Nanosheets - Shen, Chia‐An (Angew Chem Int Ed Engl, 2021)
A bis(squaraine) dye equipped with alkyl and oligoethyleneglycol chains was synthesized by connecting two dicyanomethylene substituted squaraine dyes with a phenylene spacer unit. The aggregation behavior of this bis(squaraine) was investigated in non‐polar toluene/tetrachloroethane (98:2) solvent mixture, which revealed competing cooperative self‐assembly pathways into two supramolecular polymorphs with entirely different packing structures and UV/Vis/NIR absorption properties. The self‐assembly pathway can be controlled by the cooling rate from a heated solution of the monomers. For both polymorphs, quasi‐equilibrium conditions between monomers and the respective aggregates can be established to derive thermodynamic parameters and insights into the self‐assembly mechanisms. AFM measurements revealed a nanosheet structure with a height of 2 nm for the thermodynamically more stable polymorph and a tubular nanorod structure with a helical pitch of 13 nm and a diameter of 5 nm for the kinetically favored polymorph. Together with wide angle X‐ray scattering measurements, packing models were derived: the thermodynamic polymorph consists of brick‐work type nanosheets that exhibit red‐shifted absorption bands as typical for J‐aggregates, while the nanorod polymorph consists of eight supramolecular polymer strands of the bis(squaraine) intertwined to form a chimney‐type tubular structure. The absorption of this aggregate covers a large spectral range from 550 to 875 nm, which cannot be rationalized by the conventional exciton theory. By applying the Essential States Model and considering intermolecular charge transfer, the aggregate spectrum was adequately reproduced, revealing that the broad absorption spectrum is due to pronounced donor‐acceptor overlap within the bis(squaraine) nanorods. The latter is also responsible for the pronounced bathochromic shift observed for the nanosheet structure as a result of the slip‐stacked arranged squaraine chromophores.